2003
DOI: 10.1086/376469
|View full text |Cite
|
Sign up to set email alerts
|

Color Gradients in Early-Type Galaxies in Abell 2199

Abstract: We performed B and R band surface photometry for E/S0 galaxies in a nearby rich cluster ABELL 2199 to investigate their B − R color gradients (d(B − R)/d log r).Our aims are to study statistical properties of the color gradients and, by comparing them with those in less dense environments, to examine environmental dependence of color gradients in elliptical galaxies. We studied the distribution of the B − R color gradients in the cluster ellipticals and found that the mean value of the color gradients is −0.09… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
58
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 57 publications
16
58
0
Order By: Relevance
“…Tamura & Ohta 2003;Wu et al 2005;Brough et al 2007;Reda et al 2007) as well as in recent simulations (e.g. Hirschmann et al 2015).…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…Tamura & Ohta 2003;Wu et al 2005;Brough et al 2007;Reda et al 2007) as well as in recent simulations (e.g. Hirschmann et al 2015).…”
Section: Methodsmentioning
confidence: 58%
“…Saglia et al 2000;Tamura & Ohta 2003). For example, Kuntschner et al (2010) found a mean ∇ Z = −0.25 ± 0.11 and mean ∇ age = 0.02 ± 0.13 for galaxies with age > 8 Gyr.…”
Section: Implications and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Early type galaxies (e.g., Es and S0s) typically have almost flat and red profiles, common among the red and dead objects (Tamura & Ohta 2003;Wu et al 2005). Differently from the ETGs, irregular galaxies are characterized by an almost flat blue profile reflecting their lack of dust and their ongoing SF activity at all radii (Fig.…”
Section: Radial Color Profilesmentioning
confidence: 99%
“…Although color gradients in nearby late-type galaxies (LTGs) appear to be dominated by the fact that on average their bulges are redder than their disks, LTGs show age, metallicity, and dust gradients because of the interplay among dust content, stellar feedback, bursts of star formation, and stellar migration (Gonzalez-Perez et al 2011). Earlier studies have claimed a weak correlation of color gradients with the physical properties of local galaxies (e.g., mass, luminosity, etc., Peletier et al 1990; Kobayashi & Arimoto 1999;Tamura & Ohta 2003). Recent studies based on larger and homogeneous samples of galaxies in SDSS have found that color gradients in local galaxies are closely correlated with their stellar masses, luminosities, sizes, and residual star formation (e.g., Suh et al 2010;Tortora et al 2010; Pan et al 2015).…”
Section: Introductionmentioning
confidence: 99%